Altered striatal functional connectivity and structural dysconnectivity in individuals with bipolar disorder: A resting state magnetic resonance imaging study - Okanda Nyatega, Charles; Qiang, Li; Jajere Adamu, Mohammed; Bello Kawuwa, Halima (Frontiers in Psychiatry, 2022)
Objective: Bipolar Disorder (BD) is a mood swing illness characterized by episodes ranging from depressive lows to manic highs. Although the specific origin of BD is unknown, genetics, environment, and changes in brain structure and chemistry may all have a role. Through magnetic resonance imaging (MRI) evaluations, this study looked into functional abnormalities involving the striatum between BD group and healthy controls (HC) and compared the whole-brain gray matter (GM) morphological patterns between the groups Methods: We applied sliding windows to functional magnetic resonance imaging (fMRI) data from 49 BD patients and 44 HCs to generate temporal correlations maps to determine strength and variability of the striatum-to-whole-brain-network functional connectivity (FC) in each window whilst also employing Voxel-Based Morphometry (VBM) to high-resolution structural MRI data to uncover structural differences between the groups. Results: Our analyses revealed increased striatal connectivity in three consecutive windows 69, 70 and 71 (180, 182 and 184 seconds) in individuals with BD (p < 0.05; Bonferroni corrected) in fMRI images. Moreover, the VBM findings of structural images showed gray matter (GM) deficits in the left precentral gyrus and middle frontal gyrus of the BD patients (p = 0.001, uncorrected) when compared to HCs. Variability of striatal connectivity did not reveal significant differences between the groups. Conclusions: These findings revealed that BD was associated with a weakening of the precentral gyrus and middle frontal gyrus, also implying that bipolar illness may be linked to striatal functional brain alterations.